Efektivitas Model Pembelajaran Kooperatif Tipe Team Assisted Individualization dengan Pendekatan Matematika Realistik - Muhammad Darwis; Awi; Muhaimin Akhwan Akib (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2017)
This research aims to determine the effectiveness of the cooperative learning model type team assisted individualization (TAI) with realistic mathematic approach at Grade VII SMP Negeri in Sengkang. The population of this research were all students of Grade VII in one of SMP Negeri in Sengkang and one class selected randomly as the research sample. Data collection was performed by using the observation sheets of learning accomplishment, learning achievement test, observation sheet of students’ activity and questionnaire of students’ responses. Descriptive statistical analysis of the results showed: (1) Percentage of learning accomplishment approach is 95% ( well done), (2) the average of pretest is 24,32 and the average of posttest is 83,92, (3) classical completeness is reached 86%, (4) the average normalized gain is 0,78 who are at high category, (5) Percentage of students’ activity is 92%, (6) the average percentage of students who gave positive response to the implementation of learning is 89%. Inferential analysis results showed: (1) the average percentage of students who is taught approach greater than 75, (2) the average value of normalized gain greater than 0,3. From these results it can be concluded that learning with cooperative learning model type TAI with realistic mathematic approach effective used in students at Grade VII SMP Negeri in Sengkang